AKTUALISASI DAKWAH TRANSFORMATIF DI MASA PANDEMI COVID-19 - Irfan Achfandhy, Mochammad (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
The problem of violating the Covid-19 health protocol in religious activities which is the cause of the emergence of a new cluster of the spread of the virus cannot be separated from the role of Islamic Religious Trainers (Penyuluh Agama Islam). Da'wah as the main task of Islamic extension agents is very important in fostering society and shaping social transformation in the form of changing habit patterns according to the Covid-19 protocol. This study aims to elaborate on the actualization of the dakwah carried out by the Penyuluh Agama Islam in campaigning the Covid-19 health protocol and shaping social transformation. The research method used a qualitative approach with a case study strategy. The data were obtained from the results of in-depth interviews and conducting field observations on the da'wah activities of the Penyuluh Agama Islam, Kalasan District, Sleman Regency during the Covid-19 pandemic. The results showed that the preaching messages of the Penyuluh Agama Islam were oriented to social values, carried out advocacy to the affected community, chose an interactive dialogue communication strategy, built stakeholders with related parties and formed a special organization for handling people affected by Covid-19. The contribution of this research is that the overall actualization of the preaching of the Penyuluh Agama Islam during the Covid-19 pandemic was carried out with model assistance or assistance to realize social transformation, especially in religious activities